Stepping Motor Subdividing Drive System Design Based on FPGA - Zongzuo Yu; Gaizhi Guo (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The design idea to implement multi-subdividing drive system for stepping motor based on Field-Programmable Gate Array chip was proposed in this paper. On a piece of EPF10K10LC84-15, the system module was accomplished using Very-High-Speed Integrated Circuit Hardware Description Language and graph editor. The simulation results were shown on the platform MAX+plusⅡ. This method could control the stepper motor subdivision without external digital to analog converter, which made the circuit structure be greatly simplified. And the experiment results proved that this method was also with high control precision and good effect, so it was much better than the Micro Control Unit control method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3047